A case report of successful pregnancy and delivery after peritoneal dialysis in a patient misdiagnosed with primary infertility. Issue 26 (June 2018) - Choi, Chi-Young; Cho, Nam-Jun; Park, Samel; Gil, Hyo Wook; Kim, Yun-Sook; Lee, Eun Young
Abstract: Rationale: Currently, 15% of women in fertility age are infertile and the frequency is increasing. Among the various causes of infertility, end-stage renal disease (ESRD) has been shown to decrease the frequency of pregnancies compared with normal females. However, dialysis of patients with ESRD increases the likelihood of pregnancy. Herein, we report successful pregnancy and delivery after peritoneal dialysis in a patient who was misdiagnosed as primary infertility. Patient concerns: A 37-year-old female who was unaware of her ESRD was misdiagnosed with primary infertility. After undergoing artificial insemination, she was referred to department of internal medicine because of generalized edema, dyspnea, nausea, vomiting, and poor oral intake. After evaluation, she was diagnosed with ESRD and initiated peritoneal dialysis. Diagnoses: The patients was on peritoneal dialysis for a year and discovered that she was pregnant. Interventions: During pregnancy, the patient maintained a residual urine output, BUN levels below 50 mg/dL, controlled blood pressure and a targeted hemoglobin range. She obtained adequate calories and protein and was managed by a multidisciplinary team. Outcomes: The patient delivered a preterm male baby with no anomalies. Lessons: ESRD should also be considered among the several causes of infertility in fertile women. If ESRD is the cause of infertility, the frequency of pregnancy increases following dialysis. If pregnancy is diagnosed early, intensive renal replacement therapy, adequate nutritional intake and regular fetal monitoring during pregnancy increase the chances of successful delivery while maintaining PD.